1994
DOI: 10.1177/106342669400200406
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Low-Income Families To Mental Health Services

Abstract: The family associate is a parent without professional mental health training who acts as a system guide to low-income families whose children have been referred to mental health services through the Early and Periodic Screening, Diagnosis and Treatment program. The family associate provides emotional support, information about mental health services and community resources, and directs assistance, such as help with transportation and child care. Based on the belief that parent-to-parent support can be a powerf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 13 publications
0
33
0
1
Order By: Relevance
“…For example, parent advocates assisted in locating families who were without phones, facilitated staff interactions with families, and assisted in the design and delivery of parent-directed services. Involvement of paraprofessionals is not uncommon in children's mental health services, most typically for children with intensive mental health needs (e.g., Hiatt et al, 1997;Koroloff, Elliott, Koren, & Friesen, 1994;Nielsen, 1995). However, to our knowledge, the present study was unique in applying this strategy to children with disruptive behavior disorder, and in involving parent advocates in a central role in the design and delivery of parent services.…”
Section: Discussionmentioning
confidence: 99%
“…For example, parent advocates assisted in locating families who were without phones, facilitated staff interactions with families, and assisted in the design and delivery of parent-directed services. Involvement of paraprofessionals is not uncommon in children's mental health services, most typically for children with intensive mental health needs (e.g., Hiatt et al, 1997;Koroloff, Elliott, Koren, & Friesen, 1994;Nielsen, 1995). However, to our knowledge, the present study was unique in applying this strategy to children with disruptive behavior disorder, and in involving parent advocates in a central role in the design and delivery of parent services.…”
Section: Discussionmentioning
confidence: 99%
“…However, early published accounts indicated that these parent advocates did not appear to significantly contribute to the observed gains in outcomes measured (Evans et al 1996). Koroloff et al (1994Koroloff et al ( , 1996 conducted a comparison study across multiple sites to examine the role of ''family associates'' in supporting ''low-income families'' with children referred to mental health services through Oregon's Early and Periodic Screening, Diagnosis and treatment (EPSDT) program. The majority of children in the study were White and between the ages of 4 and 12.…”
Section: Peer Providers As Parent Supports In Children's Mental Healthmentioning
confidence: 97%
“…The majority of children in the study were White and between the ages of 4 and 12. The intervention was intended to reduce barriers to service access (individual and systemic), increase continued service utilization, and increase caregiver empowerment (Koroloff et al 1994(Koroloff et al , 1996. Three family associates, two of whom were parents of children with mental health issues and one who had worked as a line staff in the mental health system, provided three primary types of time-limited assistance: emotional and social support; general information (e.g., system processes, mental health disorders, services, etc.…”
Section: Peer Providers As Parent Supports In Children's Mental Healthmentioning
confidence: 99%
“…Once deemed only a radical innovation for providing service to more of those in need (Albee, 1959), the use of paraprofessionals has become common practice (Cowen, 1973). There has been increasing use of paraprofessionals on college campuses and in both institutional and community settings (Carns, Carns, & Wright, 1993;Durlak, 1971;German & Jacobs, 1986;Goodman, 1990;Guerney, 1969;Hetherington, 1995;Koroloff, Elliott, Koren, & Friesen, 1994;Lenihan & Kirk, 1992;Mavis & Stoffelmayr, 1994;Ossip-Klein, Giovino, Megahed, & Black, 1991;Pruitt, Miller, & Smith, 1989). Federal legislation has encouraged the widespread use of paraprofessional personnel.…”
mentioning
confidence: 95%